Characterizing sub-glacial hydrology using radar simulations - C. Pierce; C. Gerekos; M. Skidmore; L. Beem; D. Blankenship; W. S. Lee; E. Adams; C.-K. Lee; J. Stutz (The Cryosphere, 2024)
The structure and distribution of sub-glacial water directly influences Antarctic ice mass loss by reducing or enhancing basal shear stress and accelerating grounding line retreat. A common technique for detecting sub-glacial water involves analyzing the spatial variation in reflectivity from an airborne radar echo sounding (RES) survey. Basic RES analysis exploits the high dielectric contrast between water and most other substrate materials, where a reflectivity increase ≥ 15 dB is frequently correlated with the presence of sub-glacial water. There are surprisingly few additional tools to further characterize the size, shape, or extent of hydrological systems beneath large ice masses.